Effect of Levothyroxine on Oxidative stress and Lipid Profile in Hypothyroid Patients (Ibrahim Cardiac Medical Journal, 2022)
Background & Objective: Hypothyroidism is a common endocrine disorder and requires lifelong treatment. The present study was designed to evaluate the impact of levothyroxine (LT4) on the oxidative stress and metabolic state by assessment of malondialdehyde (MDA) level along with lipid profile in hypothyroid patients.Methods: This cross-sectional analytical study was conducted in the Department of Pharmacology & Therapeutics, Rajshahi Medical College in collaboration with the Institute of Nuclear Medicine & Allied Sciences (INMAS), Rajshahi between July 2018 to June 2019 to compare malondialdehyde (MDA) level and lipid profile among hypothyroid patients, normal individuals and levothyroxine treated hypothyroid patients. The study included 20 newly-diagnosed hypothyroid patients, 20 Levo-treated hypothyroid patients and 20 healthy controls of both sexes.Result: The MDA level was significantly highest in newly diagnosed hypothyroid patients among the three groups (p < 0.001). The mean of MDA level of hypothyroid patients, LT4-treated hypothyroid patients and normal healthy controls were 10.0 ± 2.13 μmol/l, 5.88 ± 1.90 μmol/l and 2.66 ± 0.61 μmol/l respectively. Significantly higher values of total cholesterol (TC) (198.5 ± 19.2 mg/dl), triglycerides (TG) (147.0 ± 14.5 mg/dl), low density lipoprotein-cholesterol (LDL-C) (133.9 ± 19.7 mg/dl), and a significantly decreased value of high density lipoprotein-cholesterol (HDL-C) levels (35.1 ± 3.67 mg/dl) were observed in newly-diagnosed hypothyroid patients as compared to those in Levo-treated hypothyroid patients and normal healthy individuals (p = 0.009).Conclusion: The MDA level is significantly raised which suggests that people with hypothyroidism have high risk of free radical damage and risk of development of atherosclerosis, which may lead to coronary heart diseases (CHD). Treatment with LT4 significantly improves oxidative stress and corrects lipid profile but not up to the normal level. Addition of lipid lowering drugs and supplementation with antioxidants to traditional LT4 therapy can be tested to see further improvement in outcome parameters.Ibrahim Card Med J 2021; 11 (1): 48-53